Halogen-dependent electronic regulation of reactivity and acetylcholinesterase recognition in halomethyl acetates: a predictive DFT-docking framework - Abed, Mahmood Dahham Abed; Tahhan, Omar M. Saeed Younus; Fto, Ahmed Muhsin Mohammed Youns; Kebiroglu, Mehmet Hanifi; Bulut, Niyazi (Springer, 2026)
In this work, we propose a halogen-tuning framework that links electronic reactivity descriptors to enzyme recognition for halomethyl acetates (fluoromethyl, chloromethyl, and bromomethyl acetate). Density Functional Theory calculations were performed at the B3LYP/6-311G(d, p) level to explain structure property relationships across the F/Cl/Br substitution axis. Geometry optimization shows a systematic elongation of the C5-X bond (F < Cl < Br), while the ester carbonyl remains nearly invariant, suggesting a localized substituent effect. Frontier orbital energies analysis and global descriptors reveal that bromomethyl acetate is the softest and most electronically labile derivative, exhibiting the smallest HOMO-LUMO energy gap, whereas the fluorinated analogue demonstrates the highest kinetic stability. Simulated FT-IR, H-1/C-13 NMR (GIAO), and TD-DFT UV-Vis spectra provide complementary fingerprints showing halogen-driven electronic modulation. Topological analyses (MEP, DOS, RDG/NCI/DORI) map the redistribution of electron density and weak interaction regions that rationalize the observed trends. Molecular docking against acetylcholinesterase (AChE; PDB: 1EVE) indicates a monotonic enhancement of binding affinity with increasing halogen polarizability, with bromomethyl acetate exhibiting the strongest predicted affinity. Collectively, these results establish a predictive structure reactivity recognition reasoning for halomethyl acetates and support their consideration as electrophile-tuned model systems for exploring substituent-dependent recognition tendencies.
Keywords: Halomethyl Acetates; Halogen Tuning; Dft; B3Lyp; Reactivity Descriptors; Spectroscopic Simulation; Rdg/Nci/Dori; Density Of States; Molecular Docking; Acetylcholinesterase